STUDY OF AWARENESS AMONG HEALTHCARE PROVIDERS FOR THE NEED TO PERIODICALLY SCREEN RENAL FUNCTIONS IN DIABETIC PATIENTS RECEIVING METFORMIN - Hadidchi, Mohammad Shahab; Shenoy, Ujjwala V.; Thomas, Jebin Mammen; Vupputuri, Raja Sudhakar (International Journal of Current Pharmaceutical Research, 2015)
Objectives: To evaluate the awareness of serum creatinine monitoring and maximum daily dose of metformin among healthcare providers. Methods: We conducted the prospective-observational study among healthcare providers like attending physicians, resident doctors, medical students and nurses. A questionnaire with multiple choice questions was designed and circulated among various healthcare providers in a tertiary care hospital in Hoskote, Bangalore, Karnataka. The participants were unaware of the study objective. Results: Total of 100 Healthcare Providers participated in our survey. The majority of them were faculty members (attending physicians or HODs; n= 33) or resident doctors (n=50) contributed towards 83% of the participants while students (n= 7) and nurses (n= 10) were the minority participants at the hospital. Awareness of serum creatinine monitoring in patients receiving metformin in the Attending Physicians (84%) seem to be higher as compared to the Resident Doctors (72%). Medical students (14%) and nurses (30%) had a very low awareness. Awareness of maximum daily dose for metformin in the Attending Physicians (78%) seem to be higher as compared to the Resident Doctors (64%). Medical students (14%) and nurses (30%) had a very low awareness. Conclusion: Awareness of maximum daily dose of metformin and serum creatinine monitoring was high among physicians as compared to resident doctors. Nurses and medical students lacked in this knowledge. Clinical pharmacist can play a vital role by providing concise information about new drug therapies, warnings and precautions about old/new drugs to health care providers. Working together, clinical pharmacists and physicians can improve the patient care.